2018
DOI: 10.15517/ijds.v20i2.32521
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Osteoma of Mandibular Angulus: Analysis of the Literature and Report of a New Case

Abstract: Osteoma is a benign osteogenic neoplasm originating from the continuous proliferation of compact and/or cancellous mature bone. The tumor can be classified as peripheral, central or extra-skeletal regarding location and it commonly seen in the cranio-facial region especially at the skull and paranasal sinuses. The exact etiology of the tumor is still controversial; however, it is considered that infection, trauma, muscle activity contributes the occurrence of the tumor. Due to the slow growing nature of osteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Osteomas are benign neoplasm of mature bone which may be cancellous or compact. 12 Males are affected more than females with age 30-to-50-year range mentioned in literature. 13 Few articles mention no specific predilection for males over females.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomas are benign neoplasm of mature bone which may be cancellous or compact. 12 Males are affected more than females with age 30-to-50-year range mentioned in literature. 13 Few articles mention no specific predilection for males over females.…”
Section: Discussionmentioning
confidence: 99%
“…Certains auteurs ne considèrent pas l'ostéome comme étant une pathologie tumorale mais plutôt une anomalie de développement au dépend des reliquats embryonnaires cartilagineux ou périostés alors que d'autres incriminent le mécanisme de réactivation osseuse réactionnelle suite au décollement infectieux ou traumatique du périoste (oedème, hématome). Cette réaction ostéogénique est entretenue par les sollicitations mécaniques des insertions musculaires (5). Aucun facteur infectieux ou traumatique n'a été révélé chez notre patiente.…”
Section: Discussionunclassified
“…Small-sized osteomas are usually kept under observation; surgical excision is the treatment of choice when it causes disfigurement and functional disability. [ 9 ] Usually, the intraoral route is preferred because of cosmetic concerns; however, in the cases presented above, 3D-CT clearly showed the location of the lesion near the inferior border of the mandible, making it challenging for the intraoral approach. An extraoral approach was chosen to gain proper access to the lesion, which further allows proper excision of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Literature showed that the extraoral surgical approach was used when lesion affected the angle of the mandible. [ 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation